Liver Involvement in Patients with Dengue - MONA AZIZ QASIM ZAFAR ATIYA MAHBOOB, ASMA MUNIR (Journal of Fatima Jinnah Medical University, 2018)
Background: Dengue is a global health problem, endemic to most tropical and subtropical countries. Liver involvement in dengue fever is not uncommon. It is one of the predicting factors of severe dengue. Objective: To evaluate the impact of dengue virus infection on liver function tests (LFTs) of patients with dengue fever. Design: Prospective, follow up study Place and duration of study: Department of Medicine, Shaikh Zayed Medical Institute, Lahore from 5th October, 2010 to 20th November, 2010. Patients and methods: Forty-seven serologically confirmed cases were categorized into, dengue fever(DF), dengue haemorrhagic fever (DHF) and dengue shock syndrome (DSS) according to WHO guidelines and evaluated daily for 7 days to see the serial changing pattern of LFTs including serum total bilirubin (ST bilirubin), albumin, aspartate and alanine aminotransferases (AST and ALT) and alkaline phosphatase (ALP). Based on the levels of aminotransaminases degree and severity of liver damage were classified into grades A to D and severe dengue. Results: Forty-seven diagnosed cases of DF with male to female ratio 1.09:1, mean age of 31.3±15.4 years were included in the study. DF, DHF and DSS were found in 70.83%, 18.67%, 10.6% cases respectively. Maximum number of male patients belonged to second decade of life. Hepatic dysfunction in form of raised levels of ST bilirubin, AST, ALT and ALP and the decreased value of serum albumin were seen in 31.9%, 100%, 95.7%, 68.1%, 63.8% respectively. Serial reports of LFT showed ST bilirubin more than 1mg/dl in 7 patients on day 2 while highest value 8.6 on 5th day, serum albumin less than 3.5 g/dl in 13 patients on days 3 and 4, continuous increasing levels of ALP from day 1 to day 7 and decreasing levels of AST and ALT throughout the hospital stay. 13, 26 and 8 patients were classified as Grade B, C and D of liver damage. Five female patients (10.6%) had severe dengue with AST or ALT ≥1000 U/L. All patients recovered except one female who died of DSS on second day of admission. Conclusion: Liver involvement is universal in patients with DF to a variable extent. Majority of patients had mild to moderate liver dysfunction though 10% had acute hepatitis without significant complications. Serial monitoring of LFTs in these patients throughout hospital stay should be done for early diagnosis of liver dysfunction, proper management and better outcome of cases.